Evaluasi Kebutuhan Fungsional Sistem Informasi Pelaporan Kegiatan Menggunakan Metode Quality Function Deployment di BNN Kota Malang - Sinta Kurniasari; Mochamad Chandra Saputra; Admaja Dwi Herlambang (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2018)
In the information system development process, information system required the presence of definition and determination of priority functional requirements. The purpose of the definition and determination of priorities is to help organizations found out where the functional requirements are indeed important and necessary. This research was conducted on the definition of the functional requirements and the determination of priorities by using the method of Quality Functional Deployment (QFD). QFD method used to discover the functional requirements of the system based on the desires of the customer. The matrix was used in this research is the matrix of House of Quality (HoQ). This research was conducted using qualitative methods to interview informants that add up to 8 people. From the result of preparation of HoQ produced a number of 24 VoC and 28 functional requirements, as well as of the calculation of the weighted importance rating with weights relation obtained priority value for the 28 functional needs.